Kinetic and Spectroscopic Studies of the ATP:Corrinoid Adenosyltransferase PduO from Lactobacillus reuteri: Substrate Specificity and Insights into the mechanism of Co(II)corrinoid Reduction - Park, Kiyoung (2008)
The PduO-type ATP:corrinoid adenosyltransferase from Lactobacillus reuteri (LrPduO) catalyzes the formation of the essential Co–C bond of adenosylcobalamin (coenzyme B(12)) by transferring the adenosyl group from co-substrate ATP to a transient Co(1+)corrinoid species generated in the enzyme active site. While PduO-type enzymes have previously been believed to be capable of adenosylating only Co(1+)cobalamin (Co(1+)Cbl(−)), our kinetic data obtained in this study provide in vitro evidence that LrPduO can in fact also utilize the incomplete corrinoid Co(1+)cobinamide (Co(1+)Cbi) as an alternative substrate. To explore the mechanism by which LrPduO overcomes the thermodynamically challenging reduction of its Co(2+)corrinoid substrates, we have examined how the enzyme active site alters the geometric and electronic properties of Co(2+)Cbl and Co(2+)Cbi(+) by using electronic absorption, magnetic circular dichroism, and electron paramagnetic resonance spectroscopic techniques. Our data reveal that upon binding to LrPduO that was pre-incubated with ATP, both Co(2+)corrinoids undergo a partial (~40–50%) conversion to distinct paramagnetic Co(2+)species. The spectroscopic signatures of these species are consistent with essentially four-coordinate, square-planar Co(2+) complexes, based on a comparison with the results obtained in our previous studies of related enzymes. Consequently, it appears that the general strategy employed by adenosyltransferases for effecting Co(2+)→Co(1+) reduction involves the formation of an “activated” Co(2+)corrinoid intermediate that lacks any significant axial bonding interactions, so as to stabilize the redox-active, Co 3d(z(2))-based molecular orbital.